Strategi Pengawasan BAKAMLA Zona Maritim Barat dalam Pengamanan dan Keselamatan di Wilayah Perairan Kota Batam - Gravela Melleyuandita Annisa; Raissa Sofia Martin (Social Issues Quarterly, 2022)
As the largest archipelagic country in the world, Indonesia has a very wide sea area. Indonesia has abundant natural resources. This certainly benefits Indonesia's position as a major power country in both Southeast Asia and the Asia Pacific if we are able to take advantage of it. This condition can also be a driving force for all levels of the nation's components to improve their capabilities to establish themselves as a maritime country. However, currently maritime security in Indonesia is still vulnerable due to the high level of violations that exist. This happens because in the western maritime zone there is very little supervision plus BAKAMLA personnel experience shortages so that sometimes they have to ask the Indonesian Navy for help in optimizing their performance, the strategies applied are also not efficient, so in this study we recommend what strategies should be done by BAKAMLA so that efforts to safeguard the sovereignty of the western maritime zone can be optimal.